Overcoming Tradeoffs in the Taxation of Punitive Damages - Dan Markel (Washington University Law Review, 2011)
As explained in a companion piece, there is a curious anomaly in the law of punitive damages. Jurors assess punitive damages in an amount that they believe will best “punish” the defendant. But, in fact, business defendants are not always punished to the degree that the jury intends. This is because jurors do not take into account the fact that these businesses are allowed to deduct their punitive damages awards. To solve this problem, President Obama recently proposed to make all punitive damages nondeductible, a proposal that has in the past been supported by a number of policy makers and academics. Unfortunately, the nondeductibility rule is doomed to fail in practice. Instead, the under-punishment problem is better solved through making juries and courts aware of the tax implications of punitive damages awards. While tax awareness would better address the under-punishment problem, it would at the same time increase plaintiffs’ windfalls. Sadly, there is simply no way under current punitive damages law to reduce under-punishment without simultaneously augmenting plaintiff windfalls. The tradeoff is a byproduct of the jumbled way current punitive damages law engrafts “public law” values on a private dispute resolution system not entirely capable of effectuating those values. To avoid such an unfortunate tradeoff, reform of punitive damages law would be required. This Article sketches a vision of such reform and describes its corresponding tax rules. In particular, the appropriate tax treatment of tort damages should depend on the particular purpose(s) being pursued and vindicated. In this respect, the recommendations here stake out a more nuanced middle path between those scholars and policy makers touting nondeductibility for all punitive damages and those endorsing the current rule allowing a deduction for all punitive damages paid by business defendants.
Keywords: Exemplary damages; Income tax deductions; Punitive dagames